Synthesis and Characterisation of Multivariate Metal–Organic Frameworks for Controlled Doxorubicin Absorption and Release - Ahmed Ahmed; Andrey Bezrukov; Debobroto Sensharma; Ciaran O’Malley; Michael J. Zaworotko; Davide Tiana; Constantina Papatriantafyllopoulou (Molecules)
The development of drug carriers with efficient absorption and controlled delivery properties is crucial for advancing medical treatments. Metal–organic frameworks (MOFs) with tunable porosity and a large surface area represent a promising class of materials for this application. Among them, NUIG4 stands out as a biocompatible MOF that exhibits exceptionally high doxorubicin (Dox) absorption (1995 mg dox/g NUIG4) and pH-controlled release properties. In this study, we report the synthesis and characterisation of multivariate MOFs (MV-NUIG4), which are analogues of NUIG4 that maintain the same topology while incorporating different functional groups within their framework. Eight new MV-NUIG4 MOFs have been synthesised through in situ reactions of the corresponding 4-aminobenzoic acid derivative with 4-formylbenzoic acid. The compounds were thoroughly characterised using a range of techniques, including powder X-ray diffraction, infrared spectroscopy, 1H-NMR, and single-crystal X-ray crystallography. The experimental ratio of the reagents and ligand precursors for the synthesis of MV-NUIG4 MOFs matched the ratio of the linkers in the final products. These structures incorporate additional functional groups, such as methyl and hydroxyl, in varying ratios. Computational modelling was used to provide further insight into the crystal structure of the MOFs, revealing a random distribution of the functional groups in the framework. The Dox absorption and release capacity of all analogues were studied, and the results revealed that all analogues displayed high drug absorption in the range of 1234–1995 mg Dox/g MOF. Furthermore, the absorption and release rates of the drug are modulated by the ratio of functional groups, providing a promising approach for controlling drug delivery properties in MOFs.